Determinants of Open Defecation in the Community of Kelurahan Tuah Negeri RW 01 Tenayan Raya District, Pekanbaru City in 2022: Determinan Buang Air Besar Sembarangan (BABS) Pada Masyarakat Kelurahan Tuah Negeri RW 01 Kecamatan Tenayan Raya Kota Pekanbaru Tahun 2022 - Fira Nofrizal; Risa Amalia; Agus Alamsyah (Badnur Medisa Group, 2022)
Open defecation is the act of disposing of human waste or excreta such as in fields, bushes,beaches, forests, and other open areas and allowed to spread to contaminate the soil, air, and water environment. In terms of environmental health, human waste can be a very important problem. This study aims to determine the determinants of open defecation in the community of Tuah Negeri RW 01, Tenayan Raya District, pekanbaru city. This type of research is quantitative analytic with a cross sectional design. The time of this research is from June-July 2022. The research population namely the Tuah Negeri village community RW 01 amounted to 362 families and the research sample was 125 respondents. The sampling technique is Simple Random Sampling by taking randomly. Data analysis was carried out univariate and bivariate with chi square test (α=0,05). The results of the bivariate analysis showed that there was a significant relationship between knowledge (p=0,035<α=0,05), attitude (p=0,000<α=0,05), income (p=0,011<α=0,05), latrine ownership (p=0,000<α=0,05) with open defecation. Variables knowledge, attitudes, income, latrine ownership related to open defecation in the community in RW 01. Cross sectoral collaboration is needed between the Puskesmas and the Tuah Negeri Village and Tenayan Raya Districtin increasing knowledge about the dangers of open defecation and changing the habits of people who defecate openly by providing special education to the community so that open defecation can stop.